3‑(het)aryl-3‑(2‑alkoxyphenyl)acrylonitriles and their derivatives - Шабликіна, О.; Козловська, Х.; Кузів, С.; Іщенко, В.; Хиля, В. (Київський національний університет імені Тараса Шевченка, 2017)
By reaction of 3‑(4‑nitrophenyl)- and 3‑hetaryl-2‑iminocoumarins with the various agents of alkylation a large set of 3‑(Het)aryl-3‑(2‑alkoxyphenyl)acrylonitriles were obtained. Quite a large array of 3‑(Het)aryl-3‑(2‑alkoxyphenyl)acrylonitriles is described in the literature, and it is shown wide variability of (Het)aryl substituents. But alkoksyphenyl fragment is represented mainly methoxy derivatives. It is caused primarily by major method of the synthesis of such structures, namely by the condensation of active 3‑(Het)arylacetonitriles with 2‑alkoxy salicylic aldehydes. Last compounds can be synthesized by alkylation, but owing to the reduced activity of the hydroxyl group in this case, good results can be obtained only high active agents (methyl iodide, dimethylsulfate etc.). We tried to change the order of stages: first make the condensation of salicylic aldehyde with 3‑(Het)aryl-acetonitrile and then make the reaction with agents of alkylation. High electron acceptor ability of the substituent in the 3rd position of 2‑iminocoumarins causes the lability of the cycle and reduces the nucleophility of Nitrogen, and it makes more possible O‑alkylation. This fact avoids the problems associated with active of alkylation agents and permits us to synthesize a wide range of new 3‑(Het)aryl-3‑(2‑alkoxyphenyl)acrylonitriles. If the original compound contains additional hydroxyl group, it is alkylated simultaneously with the cyclic Oxygen of 2‑iminocoumarin’s system. In this work we have studied one of the possible ways of further chemical transformation multifunctional molecules of 3‑(Het)aryl-3‑(2‑alkoxyphenyl)acrylonitriles: reduction of activated double bond by sodium borohydride action. It’s interesting, that through this reaction not only C=C bond can be saturated to C–C but ester group in alkoxyl residue can be transformed to alcohol group too.

Шляхом взаємодії 3-(4-нітрофеніл)- та 3-гетарил-2-імінокумаринів з алкілюючими агентами різної природи одержанно великий набір 2-(гет)арил-3-(2-алкоксифеніл)акрилонітрилів. Здійснено відновлення активованого подвійного зв'язку акрилонітрильного фрагменту за допомогою борогідриду натрію та показано, що дана реакція може супроводжуватися відновленням естерної групи до спиртової у випадку естеру [2-(2-R-2-ціановініл)фенокси]оцтової кислоти.
2-(гет)арил-3-(2-алкоксифеніл)акрилонітрили та їх похідні
Keywords: O-alkylation; 3-(Het)aryl-3-(2-alkoxyphenyl)acrylonitriles; reduction; 3-(Het)aryl-3-(2-alkoxyphenyl)propionitriles; 3-(Het)aryl-2-iminocoumarins; -; 3-(гет)арил-2-імінокумарини; О-алкілювання; 2-(гет)арил-3-(2-алкоксифеніл)акрилонітрили; відновлення; 2-(гет)арил-3-(2-алкоксифеніл)пропіонітрили; -